(untitled) (Quinto Sol, 2013)
The development of research in Regional History in Argentina allows us to wonder about the directions that are being defined. Once a phase of accumulation of information and well-founded descriptions has been completed, it is necessary to advance in explanations that can account for a whole range of common phenomena. In this sense, the challenge is to face generalization without losing the “flavor” of the inalienable specificities for historical knowledge.